A novel mutation of the MYH7 gene in a patient with hypertrophic cardiomyopathy - Nicholas Goel; Charles B Huddleston; Andrew C Fiore (The Turkish Journal of Pediatrics)
Hypertrophic cardiomyopathy (HCM) is a genetic disorder characterized by asymmetric cardiac hypertrophy due to inherited mutations in genes that encode sarcomeric proteins. MYH7, which encodes β-myosin heavy chain, is among the most commonly mutated genes in patients affected by HCM. We aimed to identify the specific mutation responsible for HCM in a six-month old Caucasian patient. NextGen DNA sequencing revealed a novel p.Ala1328Thr (A1328T) mutation of MYH7 in the affected patient as well as his asymptomatic father and asymptomatic brother. The clinical details of this mutation are described for the first time in this report. The genetic variant affects a residue that is highly conserved across species. Theoretical analysis suggests that A1328T is very likely deleterious to β-myosin heavy chain protein structure and function. Furthermore, this novel mutation was not observed with any significant frequency in approximately 6,500 healthy individuals of European and African American ancestry in the NHLBI Exome Sequencing Project, underlining the potential pathogenicity of this variant.